Leveraging Customers Loyalty in Telecommunication Industry: The Role of Service Quality and Customer Satisfaction a PLS Approach - Palladan, Ahmad Aliyu; Adamu Ahmad, Muhammad (International Journal of Marketing Research Innovation, 2019)
This study examines the moderating effect of customer satisfaction on the relationships between service quality dimensions and customer loyalty in mobile telecommunication industry in Nigeria. The study employed SmartPLS3 software for the analysis and hypotheses testing. The results of the study reveal that assurance, empathy, reliability and tangibility are positively related to customer’s loyalty. In addition, customer satisfaction had been found to moderate the relationship between customer loyalty and the five SERVQUAL dimensions with the exception of responsiveness and tangibility. Relationship between responsiveness and customer’s loyalty has been found to be negative. Finally, the study proposed some recommendations and implication for the study.